2020
DOI: 10.3390/foods9030377
|View full text |Cite
|
Sign up to set email alerts
|

Texture Preferences of Chinese, Korean and US Consumers: A Case Study with Apple and Pear Dried Fruits

Abstract: The present study aimed to understand the drivers of liking dried apple and pear chips with various textures among Chinese (n = 58), Korean (n = 58), and US (n = 56) consumers. The possibility of hedonic transfer from snack texture preferences to fruit-chip texture preferences was also investigated among Chinese and Koreans. Fourteen fruit-chip samples with four textural properties (crispy, puffy, soft, and jelly-like) were selected. Consumers rated their level of liking for each sample, and then they performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
0
18
0
1
Order By: Relevance
“…Texture of crackers is a relevant attribute for the sensory acceptance of the product, as consumers are looking for a product that is relatively crisp [ 44 ]. Hardness of crackers with increasing concentrations of S. perennis is represented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Texture of crackers is a relevant attribute for the sensory acceptance of the product, as consumers are looking for a product that is relatively crisp [ 44 ]. Hardness of crackers with increasing concentrations of S. perennis is represented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The importance of texture for dried fruit is especially true for dried fruit snacks. A previous texture preference study on dried apple and pear found that the Chinese, Koreans, and the U.S. consumers like crispy samples and dislike soft and jelly‐like samples (Wong, Kim, Chung, & Cho, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, in a study of texture preference of Chinese, Korean, and US consumers by Wong et al (2020) [ 9 ], the authors aimed to understand the drivers of liking dried apple and pear chips with various textures. The possibility of hedonic transfer from snack texture preferences to fruit-chip texture preferences was also investigated among Chinese and Koreans.…”
Section: A Synopsis Of Special Issue Researchmentioning
confidence: 99%
“…Specifically, we have brought together articles that encompass the wide scope of cross-cultural multidisciplinary research as alluded to above with perspectives in the space related to the determination of the key factors involved. The articles included can be considered to cover stakeholders in cross-cultural perception, from the senses, with respect to differences in sensitivity [ 7 , 8 , 9 ], on to consumer preferences [ 10 , 11 , 12 ], food pleasure and appetite [ 13 , 14 ], perception of food quality and safety [ 15 , 16 , 17 ], and finally key factors in relation to consumer adoption and label information in the market itself [ 18 , 19 ]. This collection of articles is in essence a snapshot of the wide focus and general relevance of sensory and consumer science in cross-cultural studies in food health and safety and we hope it inspires researchers to consider this very interesting and ever-growing space in their future work.…”
Section: Introductionmentioning
confidence: 99%